The Mechanisms and Triggering of Earthquakes in the Ridge-Transform Environment - Sumy, Danielle (2011)
The theory of plate tectonics introduced a paradigm shift in the way we view and study our planet. Many of the world's plate boundaries, however, are beneath our oceans making data collection, the key to furthering our knowledge about these zones, difficult. Recent advances in research vessels, seismic data acquisition techniques, and equipment built to withstand the temperatures and pressures within the oceans and on the seafloor, have made a huge impact in helping us understand the complicated structure and dynamics of our Earth. In the field of seismology, precise earthquake locations can illuminate regions of active seismic deformation, and help us better understand the orientation, mechanics, and kinematics of plate boundary zones. Although ocean bottom seismometers have been in use since the late 1930s, the instruments did not have the recording capacity and endurance to withstand being placed on the seafloor for a large span of time. Today, ocean bottom seismometers are deployed in densely spaced arrays that record seismic signals for approximately a year. The high-precision seismic data now available can help us redefine plate boundaries and further our understanding of the internal processes and deformation within these zones. In this dissertation, I aim to use ocean bottom seismometer data to explore the Pacific-North America plate boundary within the Gulf of California, and the internal workings of the 9º50'N East Pacific Rise high-temperature hydrothermal system. The first chapter of my dissertation uses data collected from an ocean bottom seismometer array deployed along the plate boundary within the Gulf of California from October 2005 to October 2006. In this study, I detect and locate ~700 earthquakes mainly located on the NW-SE striking oceanic transform faults that delineate the plate boundary. In addition, we calculate regional moment tensors for ~30 of these events, and find that the majority are right-lateral strike-slip events consistent with observed transtensional plate motion. Chapter 2 investigates the relationship between tides and ~3500 microearthquakes recorded on six ocean bottom seismometers deployed in the vicinity of the 9º50'N East Pacific Rise high-temperature hydrothermal vent system from October 2003 to April 2004. I find unequivocal evidence for tidal triggering of microearthquakes with maximum extensional stresses induced by the solid Earth tide at this site. Although tides are not the underlying cause of earthquake nucleation within the region, the modulation of microearthquakes by these small amplitude tidal stresses indicates that the hydrothermal system is a high-stress environment that is maintained at a critical state of failure due to on-going tectonic and magmatic processes. In Chapter 3, I further investigate the role of tides in triggering microearthquake activity at the 9º50'N East Pacific Rise high-temperature hydrothermal vent site, and observe systematic along-axis variations between peak microearthquake activity and maximum predicted tidal extension. I interpret this systematic triggering to result from pore-pressure perturbations propagating laterally through the hydrothermal system, and from this result and a one-dimensional poroelastic model, I provide an estimate of bulk permeability at this site. This observation may allow for more sophisticated investigations into the heat and chemical exchange between the newly formed oceanic crust and hydrothermal fluids, and may provide insight into the plumbing supporting the subsurface biosphere.